Validation of the 1,4‐butanediol thermoplastic polyurethane as a novel material for 3D bioprinting applications - Carlos Chocarro‐Wrona; Juan deVicente; Cristina Antich; Gema Jiménez; Daniel Martínez‐Moreno; Esmeralda Carrillo; Elvira Montañez; Patricia Gálvez‐Martín; Macarena Perán; Elena López‐Ruiz; Juan Antonio Marchal (Wiley, 2021)
Abstract Tissue engineering (TE) seeks to fabricate implants that mimic the mechanical strength, structure, and composition of native tissues. Cartilage TE requires the development of functional personalized implants with cartilage‐like mechanical properties capable of sustaining high load‐bearing environments to integrate into the surrounding tissue of the cartilage defect. In this study, we evaluated the novel 1,4‐butanediol thermoplastic polyurethane elastomer (b‐TPUe) derivative filament as a 3D bioprinting material with application in cartilage TE. The mechanical behavior of b‐TPUe in terms of friction and elasticity were examined and compared with human articular cartilage, PCL, and PLA. Moreover, infrapatellar fat pad‐derived human mesenchymal stem cells (MSCs) were bioprinted together with scaffolds. in vitro cytotoxicity, proliferative potential, cell viability, and chondrogenic differentiation were analyzed by Alamar blue assay, SEM, confocal microscopy, and RT‐qPCR. Moreover, in vivo biocompatibility and host integration were analyzed. b‐TPUe demonstrated a much closer compression and shear behavior to native cartilage than PCL and PLA, as well as closer tribological properties to cartilage. Moreover, b‐TPUe bioprinted scaffolds were able to maintain proper proliferative potential, cell viability, and supported MSCs chondrogenesis. Finally, in vivo studies revealed no toxic effects 21 days after scaffolds implantation, extracellular matrix deposition and integration within the surrounding tissue. This is the first study that validates the biocompatibility of b‐TPUe for 3D bioprinting. Our findings indicate that this biomaterial can be exploited for the automated biofabrication of artificial tissues with tailorable mechanical properties including the great potential for cartilage TE applications.